Role of Law Enforcement in Implementing Action Against Recidivist Performers - Anwar Nurjali; Iskandar Iskandar (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Crime is a social phenomenon that occurs in society, not a few criminals who have been sentenced to repeat crimes. The recidivist perpetrators are very disturbing to the community, so legal action must be taken against the perpetrators so that they perpetrators no longer commit crimes. This study aims to identify and analyze the factors causing the occurrence of recidivists and the efforts of law enforcement to tackle recidivist perpetrators. The method used in this paper is normative juridical. As for the study results that the factor causing the occurrence of recidivism is economic factors, criminologists and sociologists agree that the economy is the basic cause of crime. Currently, not a few criminals repeat their actions because of economic influence. Moreover, due to social and cultural factors, a person who is given a stigma or labeled a criminal will tend to commit a crime and repeat his actions. In addition to economic, social, and cultural factors, law enforcement factors also affect the occurrence of recidivists, and ineffective law enforcement will lead to repelling the tition of criminal acts. As for law enforcement efforts to prevent recidivists, namely with maximum guidance provided by prisons, this guidance can be in the form of providing spiritual guidance, care, and independence training are given to prisoners, so it is hoped that by being given guidance, prisoners who have served their sentences can return to socializing and join forces with others. Society as appropriate.